Vicios sociaes elegantes : influência médica no processo de criminalização das drogas na Primeira República - Luíza Lima Dias (2022)
The present work proposes to analyze the medical-scientific discourse on drugs in the first decades of the Brazilian republic. More specifically, the general objective is to investigate the arguments of some doctors to include the category of “toxicomania” in the list of habits considered antisocial and degenerative of the race, demanding measures on the part of jurists and legislators to combat what they understood to be a social disease of high dangerousness. With this in mind, the research starts from the analysis of the book Vícios Sociaes Elegantes (Cocaina, ether, diamba, opium and its derivatives, etc.): Clinical, medico-legal and prophylactic study, published in 1924 by the psychiatrists Pedro Pernambuco Filho and Adauto Botelho. This work was one of the relevant publications on the subject within the medical literature of the period, concentrating information on the main drugs in circulation at the time, in addition to dealing with its users and the current legislation, in dialogue with international debates. The book allows us to conclude that there was a pathologizing view of “toxicômanos”, characterizing them as sick people incapable of discernment, intellectually inferior beings who did not control their potentially criminal acts. In addition, the authors' desire is explicit for the authorities to act more energetically to legislate on the trade and use of drugs, enabling the control and treatment or punishment of subjects, depending on each case. These demands for greater government attention to health issues were also part of a larger context of expansion of medicine and its specialties, at a time of dispute between different political projects for the newly proclaimed republic. In this sense, it is essential to observe that the subjective interests of the authors also had a significant influence on their positions, considering that they carried with them professional and personal ambitions. Therefore, although presented as a neutral production and as a manual for the dissemination of medical-scientific knowledge, Vícios Sociaes Elegantes offers an opportunity to investigate the subjective and moral components present in the view of those doctors and the society that involved them.